Bake the world a better place: embedding social entrepreneurial spirit among community bakers during Covid19 in Malaysia/ Mazne Ibrahim and Nur Aliah Mansor - Ibrahim, Mazne; Mansor, Nur Aliah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Community bakers are growing in popularity. This phenomenon is prevalent since enforced lockdown because individuals are pursuing their passions and ideas in the baking business because they now have more time and money to devote to it. The discussion about community bakers and their businesses are still unclear. Thus, this article aims to understand Malaysian community bakers and their role in social entrepreneurship. Social entrepreneurship literature will be explored in discovering what makes social entrepreneurship special and what avenues exist for the community bakers’ long-term survival. This conceptual paper is based solely on reviewing and analysing literature from previous research. The method was by searching the literature published between 2020 and 2021 on the Google Scholar search engine. ‘Motivational factors’, ‘home bakers’, and ‘COVID-19’ were used as search phrases. The authors retrieved related results and those that met the search keywords, then sorted them out. 17 literature that suited the review objective were obtained. This article extends discussion concerning individual’s home bakers and forms what is now known as community bakers in Malaysia. This article suggests that community bakers’ social enterprises, despite the lack of definitive data, are still crucial to the economy amid the pandemic.